Reality on the Privacy of Personal Data in Costa Rica - Rivera Barrantes, Viviana (2019)
Privacy relates to any information that a person owns, such as his or her name, telephone number, address, e-mail address, photographs or fingerprints, as well as any other identifying information, so that if access to the data is evidenced for a purpose other than that required, its use would be illegitimate, incorrect and conduct, in addition to leading to criminal, civil and disciplinary consequences, would generate administrative consequences, such as fines or calls for attention, as determined by the Data Protection Agency of Inhabitants (PRODHAB), therefore, this article is related to privacy and protection of personal data and its importance in Costa Rica. It reflects an analysis of an individual's or organization's ability to determine what data from a computer system can be shared by third parties; shows, in addition, a series of cases focused on people accused from different areas, either through calls for harassment or because they have published data without their authorization, for that reason, this document presents both the related legislation and the case law applied by the Constitutional Chamber, as a resource and with the aim that everyone knows the legislation that exists, on what information can share and if exposed with unauthorized data have clear that the protection of Law No. 8968 on: "Protection of the person against the processing of their personal data" of public order, and guarantees respect for their rights.